The Freezing and Blocking of Water Pipes. - Carey,K L (1982)
The topic addressed in this article is the freezing and blockage of water pipes that are full, with the water either flowing or still. It has long been assumed that when the water in a pipe freezes the ice begins to form on the inside surface of the pipe and grows uniformly inward (annular growth), until finally the pipe is completely blocked. Under this hypothesis, the freezing process is fairly slow and quite predictable. The only difference between the freezing of flowing water and static water is a difference in freezing rate due to the addition of heat via the water flow. Recent studies of pipe freezing, however, have shown that the freezing process is much more complicated than this. Furthermore, the process differs substantially for still water and flowing water. Water flow can become blocked much quicker than was supposed under the earlier hypothesis, and the actual freezing process appears to be less predictable in terms of time and heat loss. These recently observed phenomena are the primary focus of this article.